How Readability Shapes Social Media Engagement - Pancer, Ethan; Chandler, Vincent; Poole, Maxwell; Noseworthy, Theodore J. (Journal of Consumer Psychology, 2019)
We suggest that text readability plays an important role in driving consumer engagement on social media. Consistent with a processing fluency account, we find that easy‐to‐read posts are more liked, commented on, and shared on social media. We analyze over 4,000 Facebook posts from Humans of New York, a popular photography blog on social media, over a 3‐year period to see how readability shapes social media engagement. The results hold when controlling for photo features, story valence, and other content‐related characteristics. Experimental findings further demonstrate the causal impact of readability and the processing fluency mechanism in the context of a fictitious brand community. This research articulates the impact of processing fluency on brief word‐of‐mouth transmissions in the real world while empirically demonstrating that readability as a message feature matters. It also extends the impact of processing fluency to a novel behavioral outcome: commenting and sharing actions.